The Roots of the Ecological Crisis in the Theological and Philosophical Landscape of Modern Civilization: An Analysis of Seyyed Hossein Nasr’s Perspective - Safdar, Saad Saood; Shams-ur-Rehmam, Ghulam (Islamic Studies, 2021)
According to contemporary Muslim philosopher and theologian Seyyed Hossein Nasr, the ecological crisis is a by-product of the modern Western worldview. The root cause of the crisis is the modern concept of nature, knowledge, and human, which has led to a spiritual crisis. For Nasr, the modern human has forgotten the vertical ascend and followed its echo and shadow in the earthly ambitions with the blind pursuit and application of modern science and technology (scientism). He desacralized knowledge and nature and sought infinite material progress in the finite world and thus brought about self-destruction in the form of ecological and environmental crises. For Nasr, the reign of quantity gave impetus to consumerism which resulted in the unprecedented destruction of nature. This paper analyzes Nasr’s views about the theological and philosophical causes of the ecological crisis and attempts to offer a realistic solution to it.